The Effectiveness of Healthcare Regulations in Preventing Malpractice in Public Hospitals - Beni Ciptawan, Beni Ciptawan; Happy Yulia Anggraeni, Happy Yulia Anggraeni (Research Horizon, 2025)
Public hospitals carry complex legal responsibilities as both medical providers and state agents ensuring citizens’ constitutional right to health. Despite reforms under Law Number 17 of 2023, Government Regulation Number 28 of 2024, and Minister of Health Regulation Number 3 of 2025, malpractice cases persist. This study aims to analyze the effectiveness of health law regulations in preventing malpractice in public hospitals. The research employs a normative legal approach using statutory, conceptual, and case study methods, with data analyzed descriptively and analytically from primary and secondary legal sources as well as five court decisions on medical negligence. The findings reveal that Indonesia’s health law regulations provide a comprehensive normative foundation but remain limited in effectiveness due to weak implementation of good governance principles, insufficient institutional supervision, and a lack of legal culture within the medical profession. Legal accountability mechanisms tend to be reactive rather than preventive. The study concludes that the effectiveness of health law regulations will be strengthened if civil, criminal, and administrative liabilities are integrated within a unified oversight system emphasizing transparency, professional development, and proactive risk prevention in public hospitals.